Creating an Opioid Recommendation Card for Trainees: Methods, Use, and Impact. Issue 5 (May 2021) - Freedman-Weiss, Mollie R.; Chiu, Alexander S.; White, Erin M.; Yoo, Peter S.
Background: In academic hospitals, surgical residents write most of the postoperative prescriptions; yet, few residents are trained on postoperative analgesia. This leads to wide variability in practices and often excess opioid prescribing. We sought to create an opioid guideline pocket card for surgical residents to access when prescribing opioids postoperatively and to evaluate the impact of this initiative. Methods: A comprehensive literature review was conducted to generate evidence-based procedure-specific opioid recommendations; additional recommendations were formulated via consensus opinion from surgical divisions at an academic institution. A pocket-sized guideline card was developed to include these procedure-specific recommendations as well as opioid guidelines for discharges after inpatient stays, non-opioid analgesic recommendations, access to opioid safety and disposal instructions for patients discharge, an equianalgesic dosing chart, and instructions for naloxone use. The card was distributed to all General Surgery house staff at a university-affiliated hospital in the spring of 2018. Following the distribution, trainees were surveyed on their use of the card. Descriptive statistics were used to analyze the survey. Results: Of 85 trainees, 62 (72.9%) responded to the survey in full; 58% use the card regularly. Of the 27 junior resident respondents, 70.4% use the card at least monthly including 48.1% who use the card daily-to-weekly. Overall, 81.6% of residents changed their opioid-prescribing practices because of this initiative and 89.8% believe the card should continue to be distributed and used. Discussion: An evidence-based guideline card for postoperative analgesia is highly valued and utilized by surgical trainees, especially those most junior in their training.